2017
DOI: 10.1002/cre2.89
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cervical auscultation in detecting the presence of material in the airway

Abstract: Several studies have investigated the accuracy of cervical auscultation (CA). However, both the sensitivities and the specificities of CA in detecting dysphagic conditions varied widely among these studies. These wide variations of the accuracy of CA might be caused by differences of the targeted sounds, such as the expiratory sound (ES) and/or swallowing sound (SS). Forty‐six dysphagic patients were served as subjects. Patients who had unoccluded tracheostoma and patients who could not follow the instructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
(29 reference statements)
1
16
0
1
Order By: Relevance
“…Instrumental investigations provide specific point-in-time diagnostic information of visual observations of penetration, aspiration and pathophysiological causes for dysphagia which underpins effective rehabilitation (Swan et al, 2019). CA provides acoustic information regarding swallow-respiratory coordination not clearly captured in VFFS or FEES (Frakking et al, 2017;Nozue et al, 2017;Yamashita et al, 2014). The CSE/review þ CA compliments holistic and person-centred care by providing opportunity for regular review of patient/ dysphagia progression and management adaptation, rather than just a snapshot of a swallow assessment.…”
Section: Cervical Auscultation and Cse/reviews: Complementing Evidence-based Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Instrumental investigations provide specific point-in-time diagnostic information of visual observations of penetration, aspiration and pathophysiological causes for dysphagia which underpins effective rehabilitation (Swan et al, 2019). CA provides acoustic information regarding swallow-respiratory coordination not clearly captured in VFFS or FEES (Frakking et al, 2017;Nozue et al, 2017;Yamashita et al, 2014). The CSE/review þ CA compliments holistic and person-centred care by providing opportunity for regular review of patient/ dysphagia progression and management adaptation, rather than just a snapshot of a swallow assessment.…”
Section: Cervical Auscultation and Cse/reviews: Complementing Evidence-based Practicementioning
confidence: 99%
“…Cervical auscultation (CA) is an adjunct to the clinical swallow evaluation and may use a stethoscope, microphone or accelerometer to listen to and interpret swallow-respiratory sounds and coordination, in paediatric and adult populations (Almeida, Ferlin, Parente, & Goldani, 2008;Borr, Hielscher-Fastabend, & Lucking, 2007;Cichero & Murdoch, 2002;Frakking, Chang, David, Orbell-Smith, & Weir, 2019;Frakking, Chang, O'Grady, David, & Weir, 2017;Lagarde, Kamalski, & van Den Engel-Hoek, 2016;Leslie, Drinnan, Finn, Ford, & Wilson, 2004;Morini ere, Boiron, Alison, Makris, & Beutter, 2008;Nozue et al, 2017;Stroud, Lawrie, & Wiles, 2002;Youmans & Stierwalt, 2011). Auscultation is regularly used in cardiac and respiratory medicine.…”
Section: Introductionmentioning
confidence: 99%
“…100,[103][104][105] Due to its inaccuracy, research has demonstrated the risk of using CA as a stand-alone tool for assessing dysphagia. 97,101,103,104,[106][107][108][109] Comparing healthy swallows and penetration-aspiration swallows with a tri-axial accelerometer, Sejdic et al showed that each axis (three anatomical directions) reported distinct information. 97 This finding suggests that the position and orientation of a sensor influence the recorded signal.…”
Section: Possible Added Value Of Acoustic Coughrelated Features In Hnc-patients With Late Radiationassociated Dysphagiamentioning
confidence: 99%
“… 100 , 103 , 104 , 105 Due to its inaccuracy, research has demonstrated the risk of using CA as a stand‐alone tool for assessing dysphagia. 97 , 101 , 103 , 104 , 106 , 107 , 108 , 109 …”
Section: Cough‐related Features As Biomarkers Of Late Rad In Hnc ‐Patientsmentioning
confidence: 99%
“…Several physical assessments and screening tests are available to identify high‐risk patients with aspiration and pharyngeal residue (Bours, Speyer, Lemmens, Limburg, & de Wit, 2009). For example, physical assessments based on neurological findings (Toscano et al, 2019), the Repetitive Saliva Swallowing Test (Oguchi et al, 2000; Oguchi, Saito, Baba, Tanaka, & Onogi, 2000), the Modified Water Swallowing Test (Osawa, Maejima, & Tanahashi, 2012), the Food Test (Tohara, Saitoh, Mays, Kuhlemeier, & Palmer, 2003), and cervical auscultation (Nozue et al, 2017) are often performed to assess aspiration and pharyngeal residue. These methods can be applied to not only patients with dysphagia in hospitals but also in nursing homes and home care settings.…”
Section: Introductionmentioning
confidence: 99%